MODERASI BERAGAMA DAN MERDEKA BELAJAR: STUDI PRILAKU MODERAT MAHASISWA IAIN PEKALONGAN - Aris Priyanto; Mita Mahda Saputri; Rizki Fauzi (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2021)
This article describes the moderate behavior of students in religion in the context of independent learning by taking a case study of IAIN Pekalongan students.Moderate religious behavior is very important for students.Students are expected to be uswatun khasanah(good role models) in building religious character for this nation's generation.The religious character of students will make this nation have a strong power in upholding Islamic teachings properly and correctly.Articles use descriptive method, namely describing various forms of moderate religious behavior carried out by IAIN Pekalongan students.Various student religious behaviors were observed, recorded, collected and described as an effort to find the data being studied.The results of this study indicate that students who practice religion moderately have:1) good and right spirituality,2) more tawasuth, tawazun, ta'adul, and tasamuh,3) feel the comfort of learning (Freedom of Learning).